Impact of multi-micronutrient supplementation on lipidemia of children and adolescents. Issue 7 (July 2020) - Chakrabarti, Anirikh; Eiden, Michael; Morin-Rivron, Delphine; Christinat, Nicolas; Monteiro, Jacqueline P.; Kaput, Jim; Masoodi, Mojgan
Summary: Background: Micronutrient supplementation has been extensively explored as a strategy to improve health and reduce risk of chronic diseases. Fat-soluble vitamins like A and E with their antioxidant properties and mechanistic interactions with lipoproteins, have potentially a key impact on lipid metabolism and lipidemia. Objective: The impact of micronutrients on lipid metabolism requires further investigation including characterization of plasma lipidome following supplementation and any cause-effect on circulating lipids. Design: In this study, we elucidate the effect and associations of a multi-micronutrient intervention in Brazilian children and teens with lipoprotein alterations and lipid metabolism. Results: Our analysis suggests a combination of short and long-term impact of supplementation on lipid metabolism, potentially mediated primarily by α-tocopherol (vitamin E) and retinol (vitamin A). Among the lipid classes, levels of phospholipids, lysophospholipids, and cholesterol esters were impacted the most along with differential incorporation of stearic, palmitic, oleic and arachidonic acids. Integrated analysis with proteomic data suggested potential links to supplementation-mediated alterations in protein levels of phospholipases and pyruvate dehydrogenase kinase 1 (PDK1). Conclusions: Associations between the observed differences in lipidemia, total triglyceride, and VLDL-cholesterol levels suggest that micronutrients may play a role in reducing these risk factors for cardiovascular disease in children. This would require further investigation.